Kinship, Status and Gender in South Celebes - Chabot, H.Th, (sian Studies - Book Archive pre-2000., 1995)
H.Th. Chabot's Ph.D. thesis, Verwantschap, stand en sexe in Zuid-Celebes (1950), is an important source for the anthropology of South Celebes. Chabot's study, based on fieldwork in the 1940s provides insights into social relationships in a South Celebes village, focusing on demographic and spatial data, systems of marriage and the position of women. His observations are of great value for historical-comparative work. This English translation makes Chabot's study accessible to a new generation of researchers. Added to the translation are a biography of H.Th. Chabot (1910-1970) and a biography of is scholarly work, as well as an extensive introduction by Martin Rössler and Birgit Röttger-Rössler, placing Chabot's contribution in the context of other work on Macassarese and Buginese society.